Carbon outcomes of major land-cover transitions in SE Asia: great uncertainties and REDD+ policy implications - Ziegler, A.D.; Phelps, J.; Yuen, J.Q; Webb, E.L; Lawrence, D.; Fox, J.M; Bruun, T.B.; Leisz, S.J.; Ryan, C.M.; Dressler, W.H.; Mertz, O; Pascual, U.; et al. (Wiley, 2012)
Policy makers across the tropics propose that carbon finance could provide incentives for forest frontier communities to transition away from swidden agriculture (slash‐and‐burn or shifting cultivation) to other systems that potentially reduce emissions and/or increase carbon sequestration. However, there is little certainty regarding the carbon outcomes of many key land‐use transitions at the center of current policy debates. Our meta‐analysis of over 250 studies reporting above‐ and below‐ground carbon estimates for different land‐use types indicates great uncertainty in the net total ecosystem carbon changes that can be expected from many transitions, including the replacement of various types of swidden agriculture with oil palm, rubber, or some other types of agroforestry systems. These transitions are underway throughout Southeast Asia, and are at the heart of REDD+ debates. Exceptions of unambiguous carbon outcomes are the abandonment of any type of agriculture to allow forest regeneration (a certain positive carbon outcome) and expansion of agriculture into mature forest (a certain negative carbon outcome). With respect to swiddening, our meta‐analysis supports a reassessment of policies that encourage land‐cover conversion away from these [especially long‐fallow] systems to other more cash‐crop‐oriented systems producing ambiguous carbon stock changes – including oil palm and rubber. In some instances, lengthening fallow periods of an existing swidden system may produce substantial carbon benefits, as would conversion from intensely cultivated lands to high‐biomass plantations and some other types of agroforestry. More field studies are needed to provide better data of above‐ and below‐ground carbon stocks before informed recommendations or policy decisions can be made regarding which land‐use regimes optimize or increase carbon sequestration. As some transitions may negatively impact other ecosystem services, food security, and local livelihoods, the entire carbon and noncarbon benefit stream should also be taken into account before prescribing transitions with ambiguous carbon benefits.